"COMPUTER MEDICINE'2004: CLINICAL INFORMATICS AND TELEMEDICINE" - N, N (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Abstracts from the conference "Computer Medicine'2004: Clinical Informatics and Telemedicine"